Comparative RNA-seq analysis reveals a critical role for ethylene in rose (Rosa hybrida) susceptible response to Podosphera pannosa - Liu, Xintong; Fang, Peihong; Wang, Zicheng; Cao, Xiaoqian; Yu, Zhiyi; Chen, Xi; Zhang, Zhao (Frontiers in Plant Science, 2022)
Rose is one of the most important ornamental flowers, accounting for approximately one-third of the world’s cut flower market. Powdery mildew caused by Podosphera pannosa is a devastating fungal disease in rose, mainly infecting the young leaves and causing serious economic losses. Therefore, a study on the mechanism of the fungus infecting the rose leaves and the possibility to improve resistance hereby is interesting and meaningful. Accordingly, we conducted transcriptome sequencing of rose leaves infected by P. pannosa at different time points to reveal the molecular mechanism of resistance to powdery mildew. The high-quality reads were aligned to the reference genome of Rosa chinensis, yielding 51,230 transcripts. A total of 1,181 differentially expressed genes (DEGs) were identified in leaves during P. pannosa infection at 12, 24, and 48 hpi. The transcription factors of ERF, MYB, bHLH, WRKY, etc., family were identified among DEGs, and most of them were downregulated during P. pannosa infection. The Kyoto Encyclopedia of Genes and Genomes analysis showed that the hormone signal transduction pathway, especially ethylene signal-related genes, was consistently showing a downregulated expression during powdery mildew infection. More importantly, exogenous 1-MCP (inhibitor of ethylene) treatment could improve the rose leaves’ resistance to P. pannosa. In summary, our transcriptome of rose leaf infected by powdery mildew gives universal insights into the complex gene regulatory networks mediating the rose leaf response to P. pannosa, further demonstrating the positive role of 1-MCP in resistance to biotrophic pathogens.